Slope and Line of Best Fit: A Transfer of Knowledge Case Study. (February 2017) - Nagle, Courtney; Casey, Stephanie; Moore‐Russo, Deborah
Abstract : This paper brings together research on slope from mathematics education and research on line of best fit from statistics education by considering what knowledge of slope students transfer to a novel task involving determining the placement of an informal line of best fit. This study focuses on two students who transitioned from placing inaccurate to accurate lines of best fit during a task‐based interview. The analysis focuses on describing shifts in slope reasoning that accompanied the change to accurately placed lines, and investigates factors that may have influenced the shift in reasoning. The results have implications for the teaching of both slope and the line of best fit.